2011
DOI: 10.1074/jbc.m110.174011
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Tumor Suppressor in Lung Cancer 1 (TSLC1) Binding to Differentially Expressed in Adenocarcinoma of the Lung (DAL-1/4.1B)

Abstract: Perturbed cell adhesion mechanisms are crucial for tumor invasion and metastasis. A cell adhesion protein, TSLC1 (tumor suppressor in lung cancer 1), is inactivated in a majority of metastatic cancers. DAL-1 (differentially expressed in adenocarcinoma of the lung protein), another tumor suppressor, binds through its FERM domain to the TSLC1 C-terminal, 4.1 glycophorin C-like, cytoplasmic domain. However, the molecular basis for this interaction is unknown. Here, we describe the crystal structure of a complex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Consistent with CADM1 having parallel function in ␤-cells, CADM1 coimmunoprecipitated DAL-1 (Fig. 6), a protein 4.1 family member also known as EPB41L3 and protein 4.1B and shown previously to interact with CADM1 in other cell types (10,44).…”
Section: Cadm Expression In Human and Rat Isletsmentioning
confidence: 61%
See 1 more Smart Citation
“…Consistent with CADM1 having parallel function in ␤-cells, CADM1 coimmunoprecipitated DAL-1 (Fig. 6), a protein 4.1 family member also known as EPB41L3 and protein 4.1B and shown previously to interact with CADM1 in other cell types (10,44).…”
Section: Cadm Expression In Human and Rat Isletsmentioning
confidence: 61%
“…*P Ͻ 0.05; **P Ͻ 0.01; ***P Ͻ 0.005. CADM1, as has been demonstrated in a variety of cell types, plays an essential role in cytoskeletal organization and remodeling (10,11,39,44). It helps anchor F-actin to subplasmalemmal sites and binds proteins that regulate actin cytoskeletal dynamics (11,39).…”
Section: Cadm Expression In Human and Rat Isletsmentioning
confidence: 99%
“…The authors suggested in the same report that, by analogy with TSLC1 and ezrin, GPC may bind to the C-lobe of R30 12) . This result contradicts previous reports that show that GPC binds to the α-lobe of R30 8,9) .…”
Section: Introductionmentioning
confidence: 97%
“…X-ray crystal structural analysis of a complex between ezrin and a peptide of Tumor Suppressor Lung Cancer (TSLC)-1, a transmembrane protein whose amino acid sequence is highly similar to that of GPC, has revealed that the TSLC1 peptide binds to the C-lobe of ezrin 12) . The authors suggested in the same report that, by analogy with TSLC1 and ezrin, GPC may bind to the C-lobe of R30 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mice lacking the full-length (ϳ130 kDa) isoform of 4.1B have impaired gait and motility associated with ultrastructural anomalies in myelinated axons (31,32). In both aspects of function, 4.1B interacts with cell adhesion molecules, notably CADM1/TSLC1 (8,36) in relation to tumor suppression and CASPR/paranodin/neurexin-4 (CNTP1) (37) in relation to the organization of paranodes and juxtparanodes of myelinated axons.…”
mentioning
confidence: 99%